2012
DOI: 10.5194/gmd-5-1589-2012
|View full text |Cite
|
Sign up to set email alerts
|

Coupling technologies for Earth System Modelling

Abstract: Abstract. This paper presents a review of the software currently used in climate modelling in general and in CMIP5 in particular to couple the numerical codes representing the different components of the Earth System. The coupling technologies presented show common features, such as the ability to communicate and regrid data, and also offer different functions and implementations. Design characteristics of the different approaches are discussed as well as future challenges arising from the increasing complexit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
56
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 23 publications
0
56
0
Order By: Relevance
“…It links component models together to construct a coupled model, and controls the integration of the whole coupled model (Valcke et al, 2012). A number of couplers are now available, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It links component models together to construct a coupled model, and controls the integration of the whole coupled model (Valcke et al, 2012). A number of couplers are now available, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The growing complexity of the coupling task means that couplers require more expertise to develop, and that labs can benefit by comparing their approaches, sharing lessons learnt, and re-using coupling code (Valcke et al, 2012). At the same time, there has been a move towards general reusable subcomponents (e.g., both atmosphere and ocean models using the same numerical solver), compared to earlier model generations, where the code for each component was developed entirely separately.…”
Section: Introductionmentioning
confidence: 99%
“…The challenges and intricacies of coupling technologies of earth system models were reviewed by Valcke et al (2012), who focused on the central features of different established systems consisting of data transfers, re-gridding, time step management, and parallel efficiency. Prominent examples of coupled modeling systems are the Community Climate System Model, CCSM (Gent, 2006), and the Earth System Modeling Framework, ESMF (Hill et al, 2006), which have also been shown to scale to processor numbers on the order of 10 4 .…”
Section: Introductionmentioning
confidence: 99%